"With two suitcases": Spanish Roma in Mexico - Lagunas, David (Romano džaniben, 2021)
Interview by David Lagunas with Manuel and Rafaela, a couple from the Spanish Cale community, who live between Sevilla and Mexico City. The interview covers topics such as migration and cultural identity, work, and mobility. In the introduction, the author summarizes the life of Manuel´s and Rafaela´s ancestors -- migration from Spain to South America and then through Brazil, Uruguay, Argentina, or Mexico, their subsistence strategies, and relationships with the majority. In the final remarks, David Lagunas comments on the couple´s situation during the Covid-19 pandemic.
Keywords: Cale; Mexico; migration; Spain